Pelatihan Kepada Orang Tua dalam Mengajar Anak Menulis Menggunakan Buku “Smart Writting” - Ramadhani, Dini; Nuryanis, Nuryanis; ., Sukirno (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Dedication to society is done because of the lack of parents knowledge who have early childhood in writing teaching in Gampong Meurandeh Dayah. There are still many children in elementary school who have not been fluent in writing. This dedication aims to provide knowledge about the development stages of writing skills and how to teach writing in early childhood to parents. Problem solved by 3 methods of presentation, demonstration, and practice. Presentation of explaining materials the developmental stages of early childhood writing and distributing the book "smart writting". Demonstration activities are carried out by providing examples of how to train early childhood writing skills. Lastly parents do practice with children in learning to write. The result of this devotion is that parents know how to deal with each stage of development of early childhood writing. As well as the community can utilize the book that has been designed a team of dedication that contains about the various activities that can be done in early childhood to train the ability to write their children. The implications of early childhood in Gampong Meurandeh Dayah can learn to write according to the stage of development and no longer difficult if entering primary school.